2004
DOI: 10.1385/jmn:24:2:181
|View full text |Cite
|
Sign up to set email alerts
|

Brain Injury-Dependent Expression of Activity-Dependent Neuroprotective Protein

Abstract: Activity-dependent neuroprotective protein (ADNP), a crucial brain development factor, contains a unique sequence, termed NAPVSIPQ, which protects mice against closed head injury (CHI). The aim of this study was to determine whether CHI affects ADNP mRNA expression in the injured brain hemisphere. Male C57JBL/6J mice were subjected to CHI. Brains were removed 5 h, 24 h, 7 d, and 29 d post-CHI. A comparison was made between ADNP mRNA in the injured versus the noninjured hemisphere using real-time polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…In this sense, Gozes and collaborators have reported that the ADNP expression in the inflammatorymediated closed head injured mouse model is upregulated in a delayed fashion (Zaltzman et al 2004), being partly affected by the presence of the inflammatory mediator CD11b in knockout experiments (Zaltzman et al 2005). NAP (NAPVSIPQ), identified as a potent neuroprotective octapeptide derived from ADNP after structure/activity screening of several peptides (Gozes 2007(Gozes , 2008, is also involved in the regulation of the inflammatory mediators such as TNF-α, IL-6, and IL-12 in macrophages, supporting a role as a molecule with dual immunomodulatory and neuroprotective activities (Quintana et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Gozes and collaborators have reported that the ADNP expression in the inflammatorymediated closed head injured mouse model is upregulated in a delayed fashion (Zaltzman et al 2004), being partly affected by the presence of the inflammatory mediator CD11b in knockout experiments (Zaltzman et al 2005). NAP (NAPVSIPQ), identified as a potent neuroprotective octapeptide derived from ADNP after structure/activity screening of several peptides (Gozes 2007(Gozes , 2008, is also involved in the regulation of the inflammatory mediators such as TNF-α, IL-6, and IL-12 in macrophages, supporting a role as a molecule with dual immunomodulatory and neuroprotective activities (Quintana et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies suggested very high gene conservation in mammals including humans, increased expression in malignant cells, and close association with cellular survival (5). In the mature brain, ADNP expression was modulated by injury, suggesting a potential protective effect for the protein in vivo (6,7). Additionally, ADNP expression shows sexual dichotomy and is modulated during the estrous cycle in the arcuate nucleus of the hypothalamus (8) and in the vagina (9), suggesting a potential neurotrophic/plasticity-associated effect for the protein.…”
mentioning
confidence: 96%
“…The highly conserved ADNP gene (Zamostiano et al, 2001) is abundantly expressed in the hippocampus (Bassan et al, 1999), cerebral cortex (Bassan et al, 1999;Zamostiano et al, 2001), and cerebellum (Zamostiano et al, 2001) and is modulated by injury (Zaltzman et al, 2004;Gozes et al, 2005b) and hormonal activity (Furman et al, 2005). Inhibition of ADNP expression results in cancer cell death (Zamostiano et al, 2001) and recombinant ADNP exhibits protection against severe oxidative stress in a neuronal cell model .…”
mentioning
confidence: 99%